2019
DOI: 10.2147/cmar.s212744
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sanguinarine exhibits potent efficacy against cervical cancer cells through inhibiting the STAT3 pathway in vitro and in vivo</p>

Abstract: Background Cervical cancer is the third most common malignancy among female cancer patients worldwide. Signal transducer and activator of transcription 3 (STAT3) is a transcription factor which regulates a variety of cancer cellular physiological activities including cervical cancer. Sanguinarine (SNG) is a natural plant-derived benzophenanthridine alkaloid that possesses antitumor activities in several cancer cells. However, its anticancer effect on human cervical cancer cells and the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…STAT3-mediated signaling is often associated with aberrant proliferation and therapeutic resistance of thyroid cancer cells [10,53,54]. Furthermore, STAT3 has been shown to be a major signaling molecule associated with human carcinogenesis, which also causes resistance to cancer therapy and induces stemness [55][56][57][58]; hence, the potential of SNG to suppress the activated STAT3 activity in PTC cells supports its anticancer potential, which is in agreement with previous findings [19,26]. Apoptosis, or programmed cell death, is a vital biological phenomenon essential for homeostasis; it is regulated by a number of signaling proteins, and once deregulated, it leads to the development of various pathological conditions including cancer and therapeutic resistance [59].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…STAT3-mediated signaling is often associated with aberrant proliferation and therapeutic resistance of thyroid cancer cells [10,53,54]. Furthermore, STAT3 has been shown to be a major signaling molecule associated with human carcinogenesis, which also causes resistance to cancer therapy and induces stemness [55][56][57][58]; hence, the potential of SNG to suppress the activated STAT3 activity in PTC cells supports its anticancer potential, which is in agreement with previous findings [19,26]. Apoptosis, or programmed cell death, is a vital biological phenomenon essential for homeostasis; it is regulated by a number of signaling proteins, and once deregulated, it leads to the development of various pathological conditions including cancer and therapeutic resistance [59].…”
Section: Discussionsupporting
confidence: 84%
“…The final step in the synthesis of SNG involves the conversion of precursor dihydrosanguinarine to SNG by the enzyme dihydrobenzophenanthridine oxidase. A number of studies have shown the therapeutic potential of SNG over a range of human pathological and toxicological conditions including cancer; for example, lung cancer [25], cervical cancer [26], gastric cancer [27,28], liver cancer [29,30], multiple myeloma [19], acute lymphoblastic leukemia [31], prostate cancer [32], colorectal cancer [33], ovary cancer [34] and pancreatic cancer [35]. Recently Achkar et al [36] extensively reviewed the anticancer features of SNG and, additionally, antioxidant/anti-inflammatory [37][38][39], antifungal [40,41], antibacterial [42,43], anthelmintic [44] and other pharmacological activities of SNG have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with a study in which sanguinarine exhibits potent efficacy against cervical cancer through ROS dependent mitochondrial apoptotic pathway. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Chelerythrine-induced apoptosis was accompanied by a decrease in the mitochondrial membrane potential (MMP), the release of cytochrome c, activation of caspase-3 and poly ADP-ribose polymerase (PARP), and downregulation of Bcl-2 in BGC-823 cells [59]. Sanguinarine inhibited tumor growth in vivo and in vitro in various cancers, including prostate [60], cervical [61], pancreatic [62], and colorectal cancers [63]. AsPC-1 and BxPC-3 growth were suppressed via an increase in Bax, Bid, and Bak and decreases in the antiapoptotic Bcl-2 and Bcl-xL proteins [62].…”
Section: Caspase-dependent Apoptosismentioning
confidence: 99%